Penerapan Hukum Jipen/Singer dalam Tindak Pidana Asusila Masyarakat Suku Dayak Ngaju (Study Kasus di Desa Pundu, Cempaga Hulu, Kotawaringin Timur, Kalimantan Tengah) - Nikmatul Janah, Anisa; R. Hariandja, Tioma; Alkahfi Setiawan, Sidi (Prodi Ilmu Hukum Fakultas Hukum Universitas Islam Jember, 2023)
Indonesia has a diverse population. Which are various tribes and nations and have their own characteristics. One of them is the Dayak tribe, a Kalimantan tribe who live in groups living in the interior, in the mountains, and so on. One of the sanctions owned by the Dayak tribe is called Jipen which has another name, namely Singer. The first problem is how is the application of the Jipen/Singer law in immoral crimes in the Dayak Ngaju tribe, Central Kalimantan?. Second problem What is the power of law in the application of the Jipen/Singer law in cases of immoral crimes?. Namely Jipen is a customary legal action for the Dayak tribe. Which is the application of the Jipen Law in Immoral Crimes. Traditional leaders who will singer who violate Dayak customary rules. Jipen is a punishment given to the perpetrator. Customary law is recognized by the state as legal law. In which the State recognizes customary law community units and their traditional rights, because Jipen law emerges from indigenous peoples. The power of Customary Law applied in the form of Jipen/Singer is very strong and thick.